Biomaterial aspects: A key factor in the longevity of implant overdenture attachment systems - Daou, Elie E. (J Int Soc Prev Community Dent, 2015)
BACKGROUND: New attachment systems are released for mandibular two-implant overdentures often without evidence-based support. Biomaterial aspects are now the parameters considered when choosing the appropriate attachment. Studies regarding their properties remain scarce. PURPOSE: The purpose of this review was to help the clinician in selrcting the most adapted stud attachments according evidence-based dentistry. MATERIALS AND METHODS: An electronic search was conducted using specific databases (PubMed, Medline, and Elsevier libraries). Peer-reviewed articles published in English up to July 2014 were identified. Emphasis was given on the biomaterial aspects and technical complications. No hand search was added. RESULTS: The electronic search generated 115 full-text papers, of which 84 papers were included in the review. The majority were clinical and in vitro studies. Some review articles were also considered. Papers reported survival and failures of overdenture connection systems. Emphasis was laid on attachment deformation. CONCLUSION: Implant overdentures long-term follow-up studies may provide useful guidelines for the clinician in selecting the type of attachment system and overdenture design. Locator attachments are more and more used, with lesser complications reported.